Tinjauan Pelaksanaan Program Pengelolaan Penyakit Kronis (Prolanis) pada Kejadian Hipertensi di Wilayah Kerja Puskesmas Oesapa Tahun 2024 - Jayanti Wake Lulu; Serlie K. A. Littik; Rina Waty Sirait (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Chronic disease is a major health problem that causes death worldwide, one of which is hypertension. Based on data from the Oesapa Health Center, the number of hypertension cases in 2024 was recorded at 58.96%, so it has not yet reached the set target. This study aims to determine the review of the implementation of the chronic disease management program (Prolanis) in the working area of Puskesmas Oesapa. The type of research used is qualitative with a descriptive approach. Data collection was done through in-depth interviews with 4 informants. The results of this study indicate that 1) input, the quantity of health workers is sufficient. In quality, health workers have competencies equipped with STRs, funds budgeted for prolanis activities are purely from BPJS, medical devices are still lacking, have SOPs on prolanis program services. 2) Process, before carrying out activities, a meeting is held first for planning the prolanis program, the implementation of activities runs according to the SOP, monitoring of recording and reporting is not optimal so that program coverage has not reached the set target. 3) Output, the Prolanis Program is right on target but the program coverage has not yet reached the predetermined indicators. The results of this study suggest that health workers must make home visits and monitor prolanis participants to routinely consume the drugs given and provide an understanding of the importance of maintaining a good and healthy lifestyle.